2017
DOI: 10.1136/bjophthalmol-2017-311096
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone versus observation in the treatment of acute central serous chorioretinopathy

Abstract: ChiCTR-IPR-16008428, Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…The percentage of patients achieving resolution of the disease varies in the literature, according to the main outcome measures considered and the different populations [ 18 , 21 , 23 , 24 , 28 ]. In the study by Ghadiali et al [ 19 ], the efficacy of both eplerenone and spironolactone was assessed in eyes with predominantly chronic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of patients achieving resolution of the disease varies in the literature, according to the main outcome measures considered and the different populations [ 18 , 21 , 23 , 24 , 28 ]. In the study by Ghadiali et al [ 19 ], the efficacy of both eplerenone and spironolactone was assessed in eyes with predominantly chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, the activation of choroidal mineralocorticoid receptors was shown to cause choroidal vasodilation and leakage; this phenomenon was inhibited by mineralocorticoid receptor (MR) antagonism [ 17 ]. Based on these findings, researchers investigated the role of mineralocorticoid antagonists in the treatment of CSC, reporting positive preliminary results [ 17 28 ]. Spironolactone and eplerenone are both oral-specific MR antagonists approved for several systemic disorders, and are commonly used for treating hypertension and congestive heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…During the follow-up, SFCT decreased in both of the groups, but the decrease was not significant in the control group as it was in the non-treated acute CSCR group in our study. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…A prospective, randomized study on 30 eyes with aCSC, revealed that 56% (n = 10/18) patients treated with spironolactone experienced a complete SRF resolution at two months in comparison with 8% (n = 1/12) in the control group ( p < 0.05) [ 30 ].…”
Section: Mineralocorticoid and Glucocorticoid-receptor Oral Antagomentioning
confidence: 99%